PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Sabrina, Nina Sabrina; Betri, Betri (Universitas Muhammadiyah Palembang, 2018)
The problem in this research was to find out how profitability and leverage on Islamic SocialReporting disclosure with firm size as moderation variable in companies listed in JakartaIslamic Index 2013-2017. The goal was to know the effect of profitability and leverage onIslamic Social Reporting disclosure with firm size as moderation variable. This researchincluded associative research that aimed to determine the relationship of two or morevariables and to know it’s effect. The independent variables were profitability and leverage,the dependent variable was islamic social reporting disclosure, and the moderation variablewas firm size. The research population was a company listed on the Jakarta Islamic Indexand listed on the Indonesia Stock Exchange 2013-2017. The number of samples tested in 10companies selected by purposive sampling method. Secondary data was needed as thebasis of analysis, while the data collection technique was documentation. Analysistechniques used multiple linear analysis and moderated regression analysis. The result ofthe research showed that there was a significant effect of profitability and leverage togetheron the disclosure of Islamic Social Reporting. Only prtially profitability could effect thedisclosure of Islamic Social Reporting significantly. Moderately moderating firm size variablescould strength then the relationship between profitability and leverage on disclosure ofIslamic social reporting with pure moderation.